The The Relationship between Self-Concept and Anxiety in University Students in the Health Sciences Field - Méndez Guerrero, Gabriel Nikolas (2024)
Anxiety is a prevalent problem in people's health worldwide and in its field of research it has been linked to self-concept, theorizing a relationship between the two. For this reason, the objective of this research was to determine the correlation between the dimensions of self-concept and anxiety in university students in the area of ​​Health Sciences. A quantitative investigation was carried out with an empirical study using the associative strategy with a sample of 690 students from the Faculty of Health Sciences of the Technical University of the North of Ibarra, in which the self-concept questionnaire was used. AF-5 and the Hamilton Scale translated and adapted. The study results reveal that anxiety inversely correlates with all self-concept dimensions, indicating a negative correlation between the two variables. The correlation strength is high between anxiety and emotional self-concept (rs: 0.5<0.7) and moderate with the other four self-concept factors (rs: 0.3<0.5); furthermore, there is a highly significant relationship as ρ <0.01. It is concluded that the lower the level of anxiety, the higher the level of self-concept.